PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, STRUKTUR KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI (Studi pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Aulia Ramadona; Amries Rusli Tanjung; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to determine the effect of Managerial Ownership Structure, Institutional Ownership Structure, Company Size and Leverage to Accounting Conservatism (Study in Food and Beverage Company Listed in Indonesia Stock Exchange Year 2011-2014). The population in this study are all food and beverage company in Indonesia which is still in operation during the years 2010-2014 amounted to 16 companies. Based on specified criteria, the company earned 13 is used as a sample in this study. This study uses secondary data in the form of annual financial statements. Methods of data analysis using multiple linear regression analysis. Based on the analysis, the conclusions of this research are: 1) Managerial Ownership Structure (SKM) has no significant effect on the variable Conservatism because significancy 0,250>0,05. 2) Institutional Ownership Structure (SKI) has no significant effect on the variable Conservatism because significancy 0,155>0,05. 3) Size Company has no significant effect on the variable Conservatism because significancy 0,252>0,05. 4) Leverage has significant effect on the variable Conservatism because significancy 0,000<0,05.Keywords: Structure Managerial Ownership, Institutional Ownership Structure, Company Size, Leverage and Accounting Conservatism